Influence of Spiritual Intelligence towards Employee Engagement and Intention to Stay by Generation Y Employees in the ICT Sector in Malaysia - Weeratunga, Ayshani; Singh Kartar Singh, Jugindar; Arumugam, Thilageswary (International Journal of Psychosocial Rehabilitation, 2020)
The ICT industry in Malaysia is one of primarily industry that contributes to the country’s economy. In the year of 2017, a total of RM 247.1 billion was contributed to the growth of the country. Gen Y, the Millennial accounts for 2.5 billion throughout the entire world and would form 75% of the employees by 2030. In Malaysia, the Generation Y population consist of 60% of the total employees which is increasing progressively. Nevertheless, Generation Y employees are hard to retain in an organization for a longer time period because their main concern is on short-term based job opportunities along with the higher anticipation of quick results. Hence, Generation Y employees generate a higher turnover rate which has been a challenge for organizations in retaining this workforce. The purpose of this research was to discover the Influence of spiritual intelligence towards employee engagement and intention to stay by Generation Y employees in the ICT sector in Kuala Lumpur, Malaysia. This is quantitative research, where a survey will be conducted through a questionnaire to collect the primary data from Generation Y employees in the ICT sector. Structural Equation Modelling will be utilized to assess the relationship by using the tool of SMART-PLS. The results are anticipated to provide new understandings on how Generation Y employees spiritual intelligence could emphasis on the engagement and intention to stay for a longer time period.